Unplanned Return to the Operating Room (UpROR) After Pediatric Diaphyseal Femoral Fractures. Issue 2 (February 2022) - Baghdadi, Soroush; Mahmoud, Mahmoud A.H.; Flynn, John (Jack) M.; Arkader, Alexandre
Abstract : Background: Femoral fractures are the most common cause of fracture-related admissions. Unplanned return to the operating room (UpROR) is a major event and imposes a substantial burden on the family and health care system. The purpose of this study was to determine the incidence of complications and early UpROR during the first 6 months following treatment of femoral fractures and their risk factors. Methods: In an institutional review board–approved study, a retrospective review of all patients who were treated for a femoral fracture during a 10-year period at a pediatric tertiary care center was performed. Patients less than 18 years old with a diaphyseal fracture and complete records were included, and nondiaphyseal or pathologic fractures, as well as underlying metabolic or genetic disorders, were excluded. All clinic visits in the first 6 months after treatment were reviewed, and all complications and UpRORs were extracted. Patients were grouped based on their age (below 5, 5 to 11, above 11 y old) at initial treatment, and statistical tests were used to infer differences between groups. Results: Overall, 841 fractures in 832 patients were included, with a mean age of 5.5±4.8 years fracture, of which 72% were male. A total of 106 complications (12.6%) and 45 UpRORs (5.3%) were encountered during the study period. Patients with and without UpROR had similar demographics and injury and treatment characteristics. Loss of reduction was the most common reason for UpROR (58%), followed by implant-related complications. Flexible nails had the highest risk of UpROR among patients who were initially treated surgically ( P =0.03). Conclusions: Our findings indicate that children under the age of 5 years have a 5% risk of UpROR in the first 6 months after the fracture, mainly for repeat spica casting due to loss of reduction. Patients aged 5 years or older have an ∼6% risk of UpROR, mainly related to complications of flexible nails. The findings of this study are important when consulting families on different treatments of diaphyseal femoral fractures. Level of Evidence: Therapeutic level III—retrospective cohort study.